2020
DOI: 10.1007/s13555-020-00411-w
|View full text |Cite
|
Sign up to set email alerts
|

Brodalumab to the Rescue: Efficacy and Safety of Brodalumab in Patients with Psoriasis and Prior Exposure or Inadequate Response to Biologics

Abstract: While biologic therapies for psoriasis are effective for many patients, some patients may lose response, have inadequate control of disease, or develop intolerance to certain biologic agents. It may therefore be beneficial for patients whose psoriasis fails to respond to one biologic to switch to a different biologic therapy, in particular one with a different mechanism of action. However, it remains unclear how prior biologic exposure or lack of response affects the efficacy and safety of subsequent biologics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…Brodalumab is a fully human IL-17 receptor A antagonist approved for the treatment of moderate-to-severe plaque psoriasis in adult patients who are candidates for systemic therapy or phototherapy and have failed to respond or have lost response to other systemic therapies [ 20 ]. The clinical benefit and safety profile of brodalumab are well established in patients with moderate-to-severe psoriasis [ 19 , 24 ]. In a recent systematic literature review and metaanalysis of more than 40 RCTs of psoriasis treatments, brodalumab demonstrated greater psoriasis area and severity index (PASI) response rates and had a higher likelihood of sustained PASI response rates for both short-term (16 weeks) and long-term (60 weeks) treatment of moderate-to-severe psoriasis than other biologics [ 13 , 24 ].…”
Section: Unique Mechanism Of Action Of Brodalumabmentioning
confidence: 99%
See 4 more Smart Citations
“…Brodalumab is a fully human IL-17 receptor A antagonist approved for the treatment of moderate-to-severe plaque psoriasis in adult patients who are candidates for systemic therapy or phototherapy and have failed to respond or have lost response to other systemic therapies [ 20 ]. The clinical benefit and safety profile of brodalumab are well established in patients with moderate-to-severe psoriasis [ 19 , 24 ]. In a recent systematic literature review and metaanalysis of more than 40 RCTs of psoriasis treatments, brodalumab demonstrated greater psoriasis area and severity index (PASI) response rates and had a higher likelihood of sustained PASI response rates for both short-term (16 weeks) and long-term (60 weeks) treatment of moderate-to-severe psoriasis than other biologics [ 13 , 24 ].…”
Section: Unique Mechanism Of Action Of Brodalumabmentioning
confidence: 99%
“…Although difficult-to-treat psoriasis often refers to lesions in particular areas of the body, biologic failure is another challenge in psoriasis treatment [ 19 ]. Biologic failure caused by drug ineffectiveness occurs when patients do not initially respond, lose response over time, or are intolerant to treatment; in such situations, therapy switch or adjuvant treatment is often required, which in practice is usually with a biologic that has a different mechanism of action [ 19 , 53 ].…”
Section: Brodalumab Treatment In Psoriasis Not Responsive To Previous...mentioning
confidence: 99%
See 3 more Smart Citations